Frequency, Distribution and Determinants of Obesity - Salman Khan, Moeen-Ul-Haq, Umar Badshah, Roya, Muhammad Asghar Essa, Muhammad Shafique (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Obesity is the state of the body where weight of the individual is high as compared to his/her weight. It is taken with reference to body mass index according to WHO. In this study we are going to determine the frequency, distribution and determinants of obesity in a selected area. Study Design: A cross sectional study Place and Duration: Gomal Medical College, D.I.Khan, Pakistan. 16/08/2020 to 20/05/2020 Material and Results: Out of 206 subjects, 18 (8.73%, 90% CI 5.47-11.93%) were obese, while 188 (91.3%, 90% CI 88.07-94.53%) were non obese. There is no association between obesity and sex, obesity and age groups and obesity and occupation in our population. Conclusion: The frequency of obesity was significantly less in our population than the other national and international studies. The proportion of obese men in our study is more than expected values from literature and the reverse is true for women. The proportion of obese persons in age group 19-39 years in our study is more than the expected values from literature and the reverse is true for the age group of 40-59 years. The proportion of obese office workers in our study is same as in other studies and the same is true for obese physical workers. There is no association between obesity and sex, obesity and age groups and obesity and occupation in our population. Keywords: Obesity, Obese, Healthy.